ANALISIS KOMPARASI KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH PENERAPAN SAK KONVERGENSI IFRS (Studi Kasus pada Perusahaan Farmasi yang Terdaftar di BEI) - Alin Alinda; Herma Wiharno; Teti Rahmawati (Jurnal Riset Keuangan dan Akuntansi, 2016)
Convergenceof IFRS into local accounting standards became a necessity for each country. This is due to the rapid developmental technology and globalization are demanding international accounting standards, with the aim of producing financial information with good quality and generally accepted. The application of IFRS as reporting standards is believed to improve the quality of reports keua-ngan company basis in the measurement of financial performance.The research objective was to determine the difference in financial performance as measured by the ratio of profitability, liquidity, solvency, and activities before and after the implementation of IFRS on the Company's GAAP ConvergencePharmaceuticals Listed in Indonesia Stock Exchange Period 2007-2014.The results showed that tdak there are significant differences related to the financial performance as measured by the ratio of profitability, liquidity, solvency, as well as the ratio of activity before and after the implementation of IFRS on the Company's GAAP ConvergencePharmaceuticals Listed in Indonesia Stock Exchange Period 2007-2014. Keywords: Profitability, Liquidity, Solvency, Activities